Mapping recommended strategies to promote active and healthy lifestyles through physical education classes: a scoping review - Alexsandra da Silva Bandeira; Fabricio Cesar de Paula Ravagnani; Valter Cordeiro Barbosa Filho; Victor José Machado de Oliveira; Edina Maria de Camargo; Maria Cecília Marinho Tenório; Paula Fabricio Sandreschi; Priscila Cristina dos Santos; Virgílio Viana Ramires; Pedro Curi Hallal; Kelly Samara Silva (BMC, 2022)
Abstract Background Understanding which strategies have been recommended for the promotion of active and healthy lifestyles through physical education (PE) classes can guide PE policies and practice. Therefore, we summarized worldwide recommendations regarding strategies for PE classes that have aimed to promote active and healthy lifestyles among school-aged children and adolescents. Methods The Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines were utilized. A literature search was carried out in June 2020 in eight peer-reviewed literature databases, in addition to searches in institutional and personal libraries. The eligibility criteria included any online document that included recommendations targeting any dimension of PE classes (e.g., policy and environment, curriculum, appropriate instruction, student assessment, and strategies that interact with PE) published since 2000. Results In total, 2,408 potentially eligible documents were screened. Of these, 63 were included in the final analysis. The recommended strategies were as follows: six referred to policy and environment (valuing PE, higher frequency and duration of classes, inclusive PE classes, mandatory daily classes, evaluation of PE classes, and qualified teachers), five to curriculum (structure, type of content, cross-cutting themes, and components that improve PE classes), four to appropriate instruction (promotion of physical activities, inclusion of social issues, employment of the use of innovative technologies, and organization of the teaching-learning process), and three to student assessment (understanding human movement concepts, evaluation of contents, and assessment methods to develop an active and healthy lifestyle). Conclusion Twenty-one strategies recommended for PE classes linked to five dimensions aimed at different target populations were identified. Over half were linked to the dimensions of policy and environment and appropriate instruction. PE is recommended to be mandatory and valued at all educational levels, with weekly frequency that contributes to an active and healthy lifestyle. This review shows that guaranteeing different experiences beyond sports, improving social inclusion, using innovative technologies, and providing adequate materials and spaces to be important challenges and ways to guide policies, programs, and new research in this field of knowledge. Open Science Framework Registration: https://osf.io/harwq/